2011
DOI: 10.1007/s11910-011-0214-y
|View full text |Cite
|
Sign up to set email alerts
|

Gait Abnormalities in Multiple Sclerosis: Pathogenesis, Evaluation, and Advances in Treatment

Abstract: Multiple sclerosis (MS) is a demyelinating disease of the central nervous system characterized by episodic decline in various neurologic functions. Gait dysfunction in MS is distinguished by decreased gait speed, walking endurance, step length, cadence and joint motion, as well as increased metabolic cost of walking and increased variability of gait. Standardized clinical, timed, and patient-based measures can identify MS patients with gait dysfunction, and observational gait analysis, instrumented walkways, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(98 citation statements)
references
References 47 publications
3
91
0
4
Order By: Relevance
“…Difficulty walking [1] is one of the most common problems experienced by people with Multiple Sclerosis (MS). The gait of people with MS compared to healthy individuals is characterised by reduced walking speed [2][3][4][5][6][7], which may be due to decreases in cadence [4,7],stride length [2,3,7] or step length [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulty walking [1] is one of the most common problems experienced by people with Multiple Sclerosis (MS). The gait of people with MS compared to healthy individuals is characterised by reduced walking speed [2][3][4][5][6][7], which may be due to decreases in cadence [4,7],stride length [2,3,7] or step length [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…The gait impairment characteristics such as slowed angular motion of the shank and a dragged foot might lead to the increased inaccuracy of detecting gait events using the algorithm based on shank angular velocity [43]. However, it should be noted that despite the increased error, the stride time and step time still demonstrated minimal absolute and relative error in the severe group (stride time error:10.6ms, 0.6% error; step time error: 6.5ms, 1.3% error).…”
Section: Swing Time Was the Least Accurate And Precisementioning
confidence: 99%
“…13,14 Several studies have shown that people with MS experience a range of gait abnormalities, including decreased step length, decreased cadence, reduced joint motion, and variability in other gait parameters, which can result in reduced gait speed. 3 Based on the evidence that dalfampridine-ER improves walking, it was thought that the observed clinical benefit of dalfampridine-ER might be, in part, related to changes in gait and balance. Thus, an exploratory study was designed to assess for treatment effect on measures of gait and balance parameters in patients who had been receiving dalfampridine-ER as part of their regular MS clinical care and had shown improved walking speed.…”
Section: Outcome Variablesmentioning
confidence: 99%
“…1 Gait dysfunction is common in people with MS, and ambulatory limitations have been identified as the most concerning functional limitation of the disease 2,3 ; their profound effect on function and quality of life in patients with MS contributes to the economic and societal burdens imposed by MS. [4][5][6][7] In a survey of patients with MS, 41% reported walking difficulty and 54% loss of balance. 8 In patients with MS, gait impairments may arise from deficits such as spasticity, weakness, decreased proprioception, ataxia, diminished motor control, visual disturbance, fatigue, and vestibulopathy.…”
mentioning
confidence: 99%